Educational Neuroscience Training for Teachers’ Technological Pedagogical Content Knowledge Construction - Cui, Yulu; Zhang, Hai (Frontiers in Psychology, 2021)
The attention to the laws of the brain and the mechanism of learning in the smart education era becomes the starting point for the convergence and development of education and neuroscience, which also inspired educational neuroscience (EN) affecting the teacher’s development. Although teachers always have a general curiosity about EN and its applications, the limited knowledge hinders their general practice, neuromyths begin to emerge, and there is no evidence to directly show the connection between EN and teachers’ technological pedagogical content knowledge (TPACK) knowledge. Based on an EN teacher training program for 216 teachers, this study verifies that EN training programs can promote teachers’ understanding of EN-related knowledge, and EN is also correlated to teachers’ TPACK. However, the EN training program does not promote high well-being and satisfaction. The research also analyzes the process of teachers’ EN knowledge dissemination based on interviews, and the research conclusion can further reveal the necessity of EN training for teachers in the future.